НАПРЯМКИ ГУМАНІСТИЧНОГО ВИХОВНОГО ПРОЦЕСУ В СИСТЕМІ ЗАОЧНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2008)
The aim of this article is to determine possible problems and priority tendencies of forming human behaver system for student of distance reportment.